The Utilization of Moodle-Based Learning Management System (LMS) in Learning Mathematics and Physics to Students Cognitive Learning Outcomes - Fatmi, Nuraini; Muhammad, Iryana; Muliana, Muliana; Nasrah, Sayni (Universitas Malikussaleh, 2021)
This study aims to determined whether there was an increase in student cognitive learning outcomes through the use of a Moodle-based Learning Management System in mathematics and physics learning.. This type of research uses a pre experimental design. The population in this study were students of Babussalam SMKS, while the sample was class XI students of the Babussalam North Aceh Islamic Boarding School. Based on the results of the analysis and discussion of research data, The percentage of the number of students who met the completeness criteria in the physics class was 67% while in the mathematics class it was 91%. The average N-gain of cognitive learning outcomes for mathematics class was 0.6, higher than the N-gain average for Physics subjects, 0.475. This is because physics learning is not sufficiently taught through the delivery of material through Moodle, but must involve students in learning with a scientific approach. In this study, Moodle has not optimally integrated learning activities with a scientific approach so that cognitive learning outcomes have not reached the expected targets in physics subjects and learning is not sufficiently taught through the delivery of material through Moodle, but must involve students in learning with a scientific approach. In this study, Moodle has not optimally integrated learning activities with a scientific approach so that cognitive learning outcomes have not reached the expected targets in physics subjects.. In this study, Moodle has not optimally integrated learning activities with a scientific approach so that cognitive learning outcomes have not reached the expected targets in physics subjects.